2015
DOI: 10.1002/cncr.29493
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor exon 20 insertions in advanced lung adenocarcinomas: Clinical outcomes and response to erlotinib

Abstract: Background EGFR exon 20 insertions (exon20ins) represent approximately 10% of EGFR-mutant lung adenocarcinomas and are associated with resistance to EGFR tyrosine kinase inhibitors (TKIs). Clinical outcomes compared to patients with sensitizing EGFR mutations are not well-established. Methods Patients with stage IV lung adenocarcinomas with EGFR exon20ins were identified through routine molecular testing. Clinico-pathologic data were collected. We measured overall survival (OS) from diagnosis of stage IV dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
168
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(187 citation statements)
references
References 37 publications
(113 reference statements)
11
168
1
2
Order By: Relevance
“…In particular, the frequency of EGFR TKI-sensitizing activating mutations differs between the East Asian and the Western world 1. The incidence of exon 20 mutation in the East Asian and Western populations ranges from 0% to 5% 6,7,10,11. In our study, we also found the incidence of exon 20 mutation to be 3.5%.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…In particular, the frequency of EGFR TKI-sensitizing activating mutations differs between the East Asian and the Western world 1. The incidence of exon 20 mutation in the East Asian and Western populations ranges from 0% to 5% 6,7,10,11. In our study, we also found the incidence of exon 20 mutation to be 3.5%.…”
Section: Discussionsupporting
confidence: 61%
“…In our series, the S768 I c. 2303 G>T was the most common mutation found. However, in other series (which have reported the mutation types in detail), the most common mutations found were D770_N771insSVD6 and S768_D770dupSVD (Wu) and V769_D770insASV 9. The poor outcomes seen in our series may be a reflection of the different biology of the mutation types.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…This is also particularly relevant for patients harboring EGFR exon 20 insertion mutations, which are known to be activating, but for which strong evidence supports de novo resistance to EGFR tyrosine kinase inhibitors (TKIs), including third-generation mutant-specific inhibitors (19,20 ). It is unclear from the The importance of proper variant classification in recruitment for clinical trials is also highlighted by the example of a retrospective clinical trial correlating response to MET-targeted therapy in gastric and esophageal cancer to the presence of MET proto-oncogene, receptor tyrosine kinase (MET) alterations.…”
Section: Gene Variant Nomenclaturementioning
confidence: 99%